The Effects of Pseudomagnetic Fields on Plasmon–Phonon Hybridization in Supported Graphene Probed by a Moving Charged Particle - Bai, Xiang-Jia; Zhang, Ying-Ying; Mišković, Zoran L.; Radović, Ivan; Li, Chun-Zhi; Song, Yuan-Hong (Plasmonics (Norwell, Mass.), 2021)
We analyze the effects of the strain-induced pseudomagnetic field on the subthreshold mechanism of hybridization taking place between the Dirac plasmon in graphene and the surface optical phonon modes in a nearby substrate. It is shown that the pseudomagnetic field exerts quite strong influence on the oscillatory pattern in the total potential in the plane of graphene, as well as on the stopping and the image forces on a charge, which moves parallel to the graphene at a speed below the Fermi velocity, specially for small graphene–substrate gap sizes. One may conclude that the subthreshold mechanism of the plasmon–phonon hybridization can be controlled by varying the pseudomagnetic field strength and the doping density in graphene.